2018
DOI: 10.3390/jcm7040071
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Autism Spectrum Disorder and Post Traumatic Stress Disorder: Two Clinical Cases

Abstract: Autism spectrum disorder (ASD) is estimated to affect one in 68 children. Given the increase in both prevalence and awareness of ASD, it is critical to provide accurate and timely diagnosis. However, ASD often co-occurs with other disorders, making diagnosis difficult. The objective of the current case study was to provide two examples of differential diagnosis in ASD and post-traumatic stress disorder (PTSD) observed in an autism clinic. In both cases, the goal was to decide whether each child should be given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
5
22
0
1
Order By: Relevance
“…Moreover, we found a prevalence of 17.1% of subjects that endorsed all the symptomatological criteria for PTSD (criteria B-E), with a significantly higher rate among AdAS Spectrum high scorers and without sex differences. The presence of higher trauma- and stress-related spectrum symptoms among subjects with AT is in line with previous literature, which reports that AT may be considered a consistent vulnerability factor for adjustment disorders and PTSD [5, 22, 30, 32, 35, 37, 43, 85]. From this point of view, our results seem to suggest that some subjects may suffer from a PTSD-like symptomatology even if they do not have a history of major traumatic events, as conceptualized yet by the Complex PTSD (cPTSD) model [41].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, we found a prevalence of 17.1% of subjects that endorsed all the symptomatological criteria for PTSD (criteria B-E), with a significantly higher rate among AdAS Spectrum high scorers and without sex differences. The presence of higher trauma- and stress-related spectrum symptoms among subjects with AT is in line with previous literature, which reports that AT may be considered a consistent vulnerability factor for adjustment disorders and PTSD [5, 22, 30, 32, 35, 37, 43, 85]. From this point of view, our results seem to suggest that some subjects may suffer from a PTSD-like symptomatology even if they do not have a history of major traumatic events, as conceptualized yet by the Complex PTSD (cPTSD) model [41].…”
Section: Discussionsupporting
confidence: 91%
“…While Mehtar and Mukaddes [30] stressed a high Prevalence of Post-traumatic Stress Disorder (PTSD) in children with ASD (around 67%), Storch et al [31] found that suicidal thoughts and behaviors were frequent in young adults with ASD, and related to the presence of depression and PTSD, suggesting that these patients may be considered as a low-resilience group with a higher vulnerability for developing trauma and stress-related disorders. However, other studies showed lower rates of comorbidity between PTSD and ASD [32]. Some authors suggested that the inconsistencies reported about the association between full-blown ASD and PTSD may be explained considering that ASD patients are frequently unable to properly report traumatic events, due to their difficulties in mentalization of traumatic contents and processing stressful situations [32-34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding trauma, cognitive rigidity, and repetitive and avoidant behaviors are found across both autism and PTSD ( Haruvi-Lamdan et al, 2017 ; Stavropoulos et al, 2018 ). Autistic people are highly vulnerable to trauma, including types of chronic trauma experiences often responsible for long-lasting cognitive and emotional effects, such as sustained bullying ( Rumball et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A taxa de prevalência pelo resultado de coorte (estudo observacional analítico) do grupo de alunos com autismo chega em 59% com um comórbido e 41% de dois ou mais comórbidos. (Stavropoulos, 2018).…”
Section: Síndrome De Asperger E Suas Característicasunclassified